Tata Kelola Irigasi Oleh HIPPA â€œTirtosariâ€di Desa Kesambirampak Kecamatan Kapongan Kabupaten Situbondo - Ernawati, Ernawati; Yuswadi, Hary (Jurnal ENTITAS SOSIOLOGI, 2018)
There are many factors that prompt the success of a food security program. One technical factor that highly supports agricultural productivity is the availability of irrigation water which is appropriate for the plant needs. In this case, irrigation cannot be separated from Irrigation Service, Agriculture Service, and HIPPA. At first, village irrigation management was carried out by an irrigation inspector called ulu-ulu who is at the lowest level in the village organization structure. In its implementation, village irrigation management experiences many obstacles, so that it causes gaps in water distribution. The purpose of this study is to analyze and describe agricultural irrigation management by HIPPA. The research used a qualitative method, and informants were determined using the purposive technique. From this study, it was found that many factors led to ineffectiveness in irrigation management. One of them is the weak coordination in HIPPA organization. This was getting worse by the appearance of money politics in water distribution among farmers and water inspector.  Keywords: Irrigation, HIPPA, Governance